Fostering Students’ Creativity in Academic Writing at Islamic Junior High School Koto Tuo, West Pasaman - Kamal, Muhiddinur; Arrifaldi, Muhammad Zainuddin bin; Rezi, Muhamad (Institut Agama Islam Negeri Imam Bonjol Padang, 2021)
The current study aimed at 1) developing a portfolio-based learning model at Madrasah Tsanawiyah, and 2) testing the validity, practicality, and effectiveness of the developed learning model. The design of the study was Research and Development (RD) using a 4-D model (defines, design, develop, and disseminate). Teachers’ books, students’ workbooks, a learning model, and validity, reliability, and practicality test were designed to support the implementation of the learning model to the teaching and learning process in the classroom. The qualitative data were collected through observation, interviews, and field notes, while the quantitative data were obtained from test and questionnaires. The data then were used to develop a final portfolio-based learning model. The findings revealed that 1) the learning instruments of portfolio-based learning model such as teachers’ book, students’ workbook, the learning manual could be adopted to implement the model; 2) the learning model was valid, practical and effective. The learning model triggered students’ engagement to study academic writing. It is concluded that the development of a portfolio-based learning model motivated students to study academic writing. Therefore, using a portfolio-based learning model was recommended to discuss further in different research.